Establishment of the design stress intensity value for the plate-type fuel assembly using a tensile test - Kim, Hyun-Jung; Tahk, Young-Wook; Jun, Hyunwoo; Kong, Eui-Hyun; Oh, Jae-Yong; Yim, Jeong-Sik (Nuclear engineering and technology, 2021)
In this paper, the design stress intensity values for the plate-type fuel assembly for research reactor are presented. Through a tensile test, the material properties of the cladding (aluminum alloy 6061) and structural material (aluminum alloy 6061-T6), in this case the yield and ultimate tensile strengths, Young’s modulus and the elongation, are measured with the temperatures. The empirical equations of the material properties with respect to the temperature are presented. The cladding undergoes several heat treatments and hardening processes during the fabrication process. Cladding strengths are reduced compared to those of the raw material during annealing. Up to a temperature of 150 °C, the strengths of the cladding do not significantly decrease due to the dislocations generated from the cold work. However, over 150 °C, the mechanical strengths begin to decrease, mainly due to recrystallization, dislocation recovery and precipitate growth. Taking into account the uncertainty of the 95% probability and 95% confidence level, the design stress intensities of the cladding and structural materials are established. The presented design stress intensity values become the basis of the stress design criteria for a safety analysis of plate-type fuels.